(untitled) (Research, Society and Development, 2023)
The indiscriminate use of antibiotics results in the non-appearance of super-resistant bacteria that cause major problems for public health. Therefore, new composts with antibacterial properties are investigated for a possible way of treatment. Brugmansia suaveolens, a plant with psychoactive properties, is endowed with chemical compounds such as alkaloids, coumarins, flavonoids, steroids and hydrocarbons and that can present antimicrobial activity. Therefore, the objective of this study is to verify the antibacterial activity of the raw aqueous solution of plant flowers. An experimental study was carried out, where it was necessary to prepare the crude aqueous solution of the Brugmansia suaveolens flowers, followed by two procedures for the evaluation of the antibacterial activity and subsequent analysis of the two results obtained. Barceu-se to antibacterial action in the species Staphylococcus aureus, presenting inhibitory halo of 25 mm in 1000mg/ml solution and 23 mm in 500mg/ml. Finally, the antimicrobial activity of the plant in Staphylococcus aureus is noted, but further studies are not necessary for a full understanding of the antimicrobial potential of the plant.